La ruta sanitaria de la seda y el poder suave de la República Popular China ante el SARS-CoV-2 - Rosas González, María Cristina; Magaña Huerta, Priscila; Haro Barón, Talia Rebeca Haro Barón (El Colegio de México A.C., 2022)
This article aims to explain the use of soft power by the People’s Republic of China (prc) by taking so-called “panda diplomacy” and global health diplomacy as examples. Using the deductive method and the support of a theoretical apparatus based on the analysis of soft power by Chinese scholars, the authors discuss the strategies Beijing uses to “win the minds and hearts” of the international community and mitigate the perception of the “Chinese threat” generated by multiple factors, including the current pandemic caused by sars-cov-2. The article concludes that through panda diplomacy and global health diplomacy, the prc has succeeded in these goals and is likely to continue to use its soft power to position itself as a great power in the 21st century.